PERTIMBANGAN HUKUM PUTUSAN HAKIM MILITER BERBASIS ASAS, TEORI DAN DOKMATIK HUKUM (Lex Jurnalica, 2019)
AbstractIn carrying out its juridical duties a judge is bound by a principle called the Ius Curia Novit principle, which means that the judge is deemed to have to know the law in each case he is handling. However, when the judges want to apply and use the laws and regulations on the cases they handle it turns out that the regulation in question does not exist or there is a legal vacuum, then what the judge needs to do is "interpretation and carrying out legal construction". Efforts that can be taken by the court or judge in terms of obtaining certainty regarding the meaning of a statutory regulation. Because a judge must have mastery of "the power of solving legal problems" to solve legal cases handled. In the outline of the duties of judges in judging a criminal case, the judge must determine the law in concreto certain events. The duty of a judge is to determine the law in concrete terms because of the demand for rights or law which is an effort to uphold the law and maintain the existence of the rule of law. The judge's decision is also referred to as a law that is often known as a "judge made law" because in a judge's decision it should contain dogmatic norms, legal theory, and legal principles. Broadly speaking, the duties of judges in the whole process of examining criminal cases are Concrete, Qualifying and Settlement. To obtain a judge's decision in accordance with the rule of law which contains "rasiodecidendi" then a judge is required to understand, among other things, philosophical thinking, namely legal Ontology, which is the legal philosophy teaching about "essence", this teaching concerns fundamental matters such as for example what are the principles of law, what is the rule of law, what is the legal and moral relationship. Epistemology of law is the teaching of the philosophy of law relating to the process of the occurrence of something (metaphilosophy). Legal axiology is the philosophy of law teachings about values, benefits, goals. This teaching concerns the legitimacy of the law, the relationship of values with propriety, equality, justice, freedom, truth and so on. A judge must understand the difference between the principle of law (the realm of legal philosophy), legal theory, legal doctrine. Besides that the judge must also understand the relationship between the three, so can also distinguish what is called a criminal act in the category of mala prohibita and mala in se.Â Keywords: dogmatic based decisions, theories, legal principlesÂ AbstrakDalam melaksanakan tugas yuridisnya seorang hakim terikat dengan suatu asas yang disebut asas Ius Curia Novit yang artinya hakim dianggap harus tahu hukum pada setiap perkara yang ditanganinya. Namun demikian, ketika hakim hendak menerapkan dan menggunakan peraturan perundang-undangan terhadap perkara yang ditanganinya ternyata peraturan yang dimaksud tidak ada atau terdapat kekosongan hukum, maka apa yang perlu dilakukan hakim tersebut yaitu â€œinterpretasi dan melakukan konstruksi hukumâ€. Upaya yang dapat ditempuh oleh pengadilan atau hakim dalam hal mendapatkan kepastian mengenai arti dari sebuah peraturan perundang-undangan. Oleh karena seorang hakim harus memiliki penguasaan â€œthe power of solving legal problemâ€œ untuk memecahkan kasus-kasus hukum yang ditanganinya. Pada garis besarnya tugas hakim dalam mengadili suatu perkara pidana, hakim harus menentukan hukumnya in concreto terhadap peristiwa tertentu. Tugas hakim adalah menentukan hukum dalam hal konkrit karena adanya tuntutan hak atau hukum yang merupakan upaya menegakkan hukum dan mempertahankan adanya tata hukum. Putusan hakim disebut juga sebagai hukum yang sering dikenal sebagai â€œjudge made lawâ€ karena di dalam putusan hakim memang seharusnya terkandung norma dogmatik, teori hukum, dan asas hukum. Secara garis besar tugas hakim dalam keseluruhan proses acara pemeriksaan perkara pidana adalah Mengkonstair, Mengkualifisir dan Menkonstituir. Untuk memperoleh putusan hakim yang sesuai dengan kaidah hukum yang didalamnya berisi â€œrasiodecidendiâ€ maka seorang hakim dituntut untuk memahami antara lain, cara berfikir filosofis, yaitu Ontologi hukum yaitu ajaran filsafat hukum tentang apa itu â€œhakikatâ€, ajaran ini menyangkut hal yang bersifat fundamental seperti misalnya apa itu asas-asas hukum, apa itu kaidah hukum, apa hubungan hukum dan moral. Epistemologi hukum yaitu ajaran filsafat hukum yang berkaitan dengan proses terjadinya sesuatu (metafilosofi). Axiologi hukum yaitu ajaran filsafat hukum tentang nilai, manfaat, tujuan. Ajaran ini menyangkut tentang legitimasi hukum, hubungan nilai dengan kepatutan, kesamaan, keadilan, kebebasan, kebenaran dan sebagainya. Seorang hakim harus memahami perbedaan antara asas hukum (ranah filsafat hukum), teori hukum, dokmatik hukum. Disamping itu hakim harus memahami pula apa hubungan diantara ketiganya, demikian pula dapat membedakan apa yang dinamakan perbuatan pidana dalam kategori mala prohibita dan mala in se.Â Kata kunci: putusan berbasis dogmatik, teori, asas hukum